Word frequency influences on the list length effect and associative memory in young and older adults. Issue 6 (3rd July 2017) - Badham, Stephen P.; Whitney, Cora; Sanghera, Sumeet; Maylor, Elizabeth A.
ABSTRACT: Many studies show that age deficits in memory are smaller for information supported by pre-experimental experience. Many studies also find dissociations in memory tasks between words that occur with high and low frequencies in language, but the literature is mixed regarding the extent of word frequency effects in normal ageing. We examined whether age deficits in episodic memory could be influenced by manipulations of word frequency. In Experiment 1, young and older adults studied short and long lists of high- and low-frequency words for free recall. The list length effect (the drop in proportion recalled for longer lists) was larger in young compared to older adults and for high- compared to low-frequency words. In Experiment 2, young and older adults completed item and associative recognition memory tests with high- and low-frequency words. Age deficits were greater for associative memory than for item memory, demonstrating an age-related associative deficit. High-frequency words led to better associative memory performance whilst low-frequency words resulted in better item memory performance. In neither experiment was there any evidence for age deficits to be smaller for high- relative to low-frequency words, suggesting that word frequency effects on memory operate independently from effects due to cognitive ageing.